De circuli magnitudine inventa : Accedunt eiusdem; Problematum quorundam illustrium constructiones - Huygens, Christiaan, 1629-1695 ([Netherlands] : Elsevier, 2014)
Christiaan Huygens (1629-1695) was born the son of diplomat Constantijn Huygens, and grew up in the company of prominent men, such as RenDescartes. After his studies in mathematics at Leiden University, he developed himself into an important astronomer. His research included the rings of Saturn and the discovery of the moon Titan. Huygens is also known as the inventor of the pendulum clock. The Elzeviers published his first book on hyperbolae, ellipses, and circles in 1651. It was followed by this treatise on the magnitude of circles in 1654.
'First published by Johannes and Daniel Elzevier in 1654. Republished by Elsevier B.V. in 2014.'
Online resource; title from PDF title page (ScienceDirect, viewed March 30, 2015).
Elsevier
Keywords: Circle -- Early works to 1800.; Mathematics -- Early works to 1800.; Circle; Mathematics; Electronic books; Early works